Handbook of spiritually integrated psychotherapies - Richards, P. Scott; Allen, G. E. Kawika; Judd, Daniel K (American Psychological Association, 2023)
"This volume shows therapists how to ethically and competently integrate spiritual perspectives and interventions into their practice in order to effectively treat clients from diverse religious, spiritual, and racial and cultural backgrounds"-- Provided by publisher.
Keywords: Psychotherapy -- Religious aspects.; Psychotherapy.; Psychology and religion.; Psychotherapy; Religion and Psychology; Psychothérapie.; Psychologie et religion.; PSYCHOLOGY / Psychotherapy / Counseling.; PSYCHOLOGY / Psychotherapy / General.; Psychotherapy -- Religious aspects